2020
DOI: 10.1007/s11739-020-02564-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2020 SARS-CoV-2 outbreak on telemedicine management of cardiovascular disease in Italy

Abstract: The Covid-19 pandemic affected large part of Italy since February 2020; we, therefore, aimed to assess the impact of 2020 SARS-CoV-2 outbreak on telemedicine management of cardiovascular disease (CVD) in Italy. We analyzed data from three telemedicine dispatch centers, one located in Genoa, serving private clients (pharmacies, general practitioners), one in Brescia, serving pharmacies, and one in Bari, serving regional public STEMI network and emergency medical service in Apulia (4 million inhabitants). Demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…A dramatic reduction of telemedicine access for CVD was observed in March 2020 in Italy compared with March 2019. The reduction was substantially consistent for all electrocardiogram findings, ACS, other acute CVD and normal [4]. This can be presumably explained by the fear of in-hospital contagion, a congestion of the emergency system overwhelmed by COVID-19 patients and an implementation of precautionary measures against contagion, leading to an increase in STEMI case fatality and major complications.…”
Section: What's Happening To Patients With Cardiovascular Disease During the Pandemic Of Covid-19supporting
confidence: 52%
“…A dramatic reduction of telemedicine access for CVD was observed in March 2020 in Italy compared with March 2019. The reduction was substantially consistent for all electrocardiogram findings, ACS, other acute CVD and normal [4]. This can be presumably explained by the fear of in-hospital contagion, a congestion of the emergency system overwhelmed by COVID-19 patients and an implementation of precautionary measures against contagion, leading to an increase in STEMI case fatality and major complications.…”
Section: What's Happening To Patients With Cardiovascular Disease During the Pandemic Of Covid-19supporting
confidence: 52%
“…The proportion of abnormal values (particularly for SpO 2 and BP) was significantly lower during the lockdown [ Figure 3D ]. However, in the same period, access to existing telemedicine and telecounseling services provided to patients daily through community pharmacies and general practices showed a dramatic drop (ranging between 49% and 85%) because of the reduced access of patients to these premises due to fear of contagion [ 109 – 111 ] [ Figure 3A ]. In the pharmacy setting, the overall proportion of abnormal tests was larger during the outbreak [ Figure 3B ]: in particular, an increase in the prevalence of abnormal ECGs due to myocardial ischemia was observed [ 109 ] .…”
Section: Experience In Different Countriesmentioning
confidence: 99%
“…The eligibility process applied to the selected references, after the elimination of the duplicated ones, returned 39 works [ 5 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], including a review focused on the relationship between telemedicine and radiotherapy [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study in [ 48 ] described a telemedicine experience in heart failure management during COVID-19. The study in [ 36 ] analyzed data from three telemedicine centers focusing on heart care. The study in [ 40 ] reported the evolution of a multidisciplinary center for myocarditis towards a telemedicine system.…”
Section: Resultsmentioning
confidence: 99%